ARTIFICIAL INTELLIGENCE AS A “BLACK BOX” OF REASON (A Historical-Philosophical and Epistemological Approach) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article explores the philosophical metaphor of the “black machine” in relation to artificial intelligence (AI) and its significance within the traditions of philosophical anthropology, epistemology, and the philosophy of mind. It examines the conceptual links between the mechanistic thinking of the Modern Age and contemporary notions of neural-network-based AI, which functions as an opaque yet efficient system. The paper argues for the necessity of rethinking fundamental philosophical concepts such as subjectivity, rationality, and explainability. Special attention is paid to the paradoxes that arise from human interaction with AI, which exhibits intellectual behavior without consciousness or self-understanding. The authors’ analysis shows that AI poses a challenge to classical epistemology, which assumes that knowledge must be meaningful, transparent, and capable of reflection. It is emphasized that the development of AI calls for a philosophical reassessment of the very notion of thinking: is knowledge possible without a subject, rationality without logic, responsibility without awareness? Ultimately, it is asserted that AI, as a “black machine,” constitutes not only a technological issue but also a deeply philosophical problem that questions the anthropocentric foundations of Western thought.
Keywords: artificial intelligence, philosophy of mind, thinking, black machine, subjectivity, rationality, reduction, contradiction, metaphysics, paradigm, evolution.